Laryngeal Tuberculosis in a Child (A Case Report) - F. X. Santoso; Esther S. I. Witono; Makmuri M. S.; Gunadi Santosa (Indonesian Pediatric Society, 1988)
Since the advent of effective antituberculous chemotherapy, laryngeal tuberculosis has become relatively uncommon, and there is a real possibility that the diagnosis may be delayed or overlooked. Data from the ENT outpatient clinic Dr. Soetomo Hospital showed a significant decrease in the prevalence of laryngeal tuberculosis, from 4. 72 o/oo in 1980 to 0.28 o/oo in 1986. This condition is usually found in adult males who have pulmonary tuberculosis. A girl with laryngeal tuberculosis is the objective of the present report. The patient was admitted with a history of chronic hoarseness. With a presumptive diagnosis of papilloma of the larynx, some biopsies were performed. The histopathologic exmamintaions suggested laryngeal tuberculosis. Additional examinations revealed a positive tubercullin test, diffuse infiltrates on both lungs and positive acid fast bacilli. Her condition improved after chemotherapy administration.